2016
DOI: 10.1038/srep20322
|View full text |Cite
|
Sign up to set email alerts
|

The Gatekeepers in the Mouse Ophthalmic Artery: Endothelium-Dependent Mechanisms of Cholinergic Vasodilation

Abstract: Cholinergic regulation of arterial luminal diameter involves intricate network of intercellular communication between the endothelial and smooth muscle cells that is highly dependent on the molecular mediators released by the endothelium. Albeit the well-recognized contribution of nitric oxide (NO) towards vasodilation, the identity of compensatory mechanisms that maintain vasomotor tone when NO synthesis is deranged remain largely unknown in the ophthalmic artery. This is the first study to identify the vasod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…The EDHF portion was mediated by CYP450 and 12/15-LOX metabolites. These findings are in agreement with previous observations in freshly isolated C57BL/6J mouse ophthalmic arteries, suggesting that overnight incubation of vessels had no marked effect on the contribution of endothelial signaling pathways to vasodilation [41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The EDHF portion was mediated by CYP450 and 12/15-LOX metabolites. These findings are in agreement with previous observations in freshly isolated C57BL/6J mouse ophthalmic arteries, suggesting that overnight incubation of vessels had no marked effect on the contribution of endothelial signaling pathways to vasodilation [41].…”
Section: Discussionsupporting
confidence: 93%
“…After preconstriction, responses to the endothelium-independent nitric oxide (NO) donor, sodium nitroprusside (SNP, 10 −9 M to 10 −4 M, Sigma-Aldrich) and to the endothelium-dependent vasodilator, acetylcholine (10 −9 M to 10 −4 M; Sigma-Aldrich) were measured. We previously demonstrated in ophthalmic arteries from mice of different genetic backgrounds, including C57BL/6J mice, that acetylcholine induces only significant vasodilation when the endothelium is intact [ 40 , 41 , 42 ]. Between each concentration–response curve, the perfusion system was washed with Krebs buffer.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the contribution of gap junctions and voltage-gated potassium channels should be explored in view of recent data in mouse OA. 43 Finally, we have shown that ET R A, ET R B, eNOS, and nNOS genes were significantly upregulated in rat optic nerve after a 14-day exposure to IH. Interestingly, this was not observed in the retina, supporting the idea that regulation of these genes is tissue-dependent, as previously shown in carotid, 44 pulmonary, 45 and brain 46 arteries.…”
Section: Discussionmentioning
confidence: 80%
“…It is possible, therefore, that a favorable effect for CUR could be only seen when a prophylactic regimen is assumed. It should also be considered that the vasodilatory response elicited by ACh is multifactorial, involving both NO-dependent and independent cellular pathways 39,40 . A differential interaction of CUR with these cellular events might possibly explain its little or no capacity in combating the reduced Ach vasodilations in MetS aortas.…”
Section: Discussionmentioning
confidence: 99%